Implementation Of Law Enforcement In Cases Of Child Neglect In The Household According To Child Protection Law (Decision Study Number: 30/Pdt.G/2020/Pn.Amb) - Loppo Halomoan Hasibuan; Hasdiana Juwita Bintang; Beby Sendy (JURNAL HUKUM SEHASEN, 2026)
Child neglect within the household constitutes one of the forms of violation of children’s rights that still frequently occurs in Indonesia. Although legal instruments are already in place, the enforcement of the law in cases of child neglect has not yet been implemented optimally. The issues examined in this study include: the general provisions concerning child neglect within the household under the Child Protection Law; the obstacles in enforcing cases of child neglect; and the efforts to optimize law enforcement in child neglect cases based on Decision Number 30/Pdt.G/2020/PN.Amb. The research method employed is normative legal research with a descriptive-analytical nature. The data consist of primary, secondary, and tertiary legal materials obtained through library research. The analysis was conducted qualitatively by examining statutory regulations, legal doctrines, legal theories, as well as relevant court decision case studies. The results of the study indicate that, normatively, child neglect has been categorized as a violation under Article 76B in conjunction with Article 77B of the Child Protection Law. However, in judicial practice, child neglect is more frequently positioned as grounds for divorce in civil cases without imposing criminal liability on negligent parents. The analysis of the Ambon District Court Decision Number 30/Pdt.G/2020/PN.Amb demonstrates a tendency for judges to focus solely on the aspect of divorce, while the issue of child neglect is not addressed at allThe conclusion of this study emphasizes that the implementation of law enforcement against child neglect within the household remains weak and lacks integration between civil and criminal aspects. Therefore, it is necessary to optimize law enforcement through preventive measures, strengthening the role of state institutions, increasing public legal awareness, and applying the principle of the best interest of the child. It is recommended that courts become more responsive to issues of child neglect, that the government strengthen regulations and inter-agency coordination, and that society take a more active role in preventing and reporting cases of child neglect.